Ontology of the Art Phenomenon in Iris Murdoch’s Fiction. - Матійчак, Альона; Нікоряк, Наталія; Тичініна, Альона (Ljubljana, 2023)
This article explores the intermedial dialogue of the arts in the oeuvre of British writer and philosopher Iris Murdoch. The ontology of the phenomenon of art and its functional meaning in Murdoch’s fiction, the specifics of the relationship between the arts in her philosophical essays and dialogues are considered from the perspective of intermediality. Based on the intermedial study methodology, Murdoch’s theoretical and philosophical views on the multifunctional nature of art, the interaction of the artist and the artwork are revealed. Key techniques of interartistic discourse, including anthroponymic allusions, are considered as intermedial markers of Murdoch’s texts, identified and explored at the level of imagological transformations. People of art: artists, artistic discourse partakers, as well as recipients of art constitute a particular kind of characters in Murdoch’s novels. Accordingly, the importance of the recipient, who acts as an essential link in the receptive matrix of “author-text-recipient-artwork,” is emphasized in the ontology of an artwork. The particular meeting point of Murdoch’s characters is the artistic topos: a museum, an exhibition, an art gallery or an artist’s house. In addition, the reader of her fiction repeatedly encounters various ekphrastic codes: the ekphrases of paintings are not only present in Murdoch’s texts, but function as anthropomorphised characters, dramatis personae, have their own space (physical and mental places) and play a crucial role in the protagonists’ lives. Consequently, we find that the use of intermedial components is one of the markers of Iris Murdoch’s idiostyle, which topicalizes important aspects of the philosophy of art and brings it into the realm of ontological questions.
Keywords: English literature; Murdoch, Iris; philosophy of art; ontology; intermediality; narrative technique; ekphrasis